Demethylation and epigenetic modification with 5-azacytidine reduces IDH1 mutant glioma growth in combination with temozolomide. Issue 2 (3rd September 2018) - Yamashita, Alex Shimura; da Costa Rosa, Marina; Borodovsky, Alexandra; Festuccia, William T; Chan, Timothy; Riggins, Gregory J
Abstract: Background: Isocitrate deyhydrogenase (IDH) mutant glioma comprises the majority of grades II–III gliomas and nearly all secondary glioblastomas. These progressive gliomas arise from mutations in IDH1 or IDH2 that pathologically produce D-2-hydroxyglutarate (2HG), which interferes with cell reactions using alpha ketoglutarate, leading to a hypermethylated genome and epigenetic dysregulation of gene expression initiating tumorigenesis. Methods: Human IDH1 wild type (wt) and IDH1 R132H cell lines and patient-derived xenografts (PDXs) were used to evaluate the FDA-approved DNA demethylating agent 5-azacytidine (5-aza). Cell growth, protein and gene expression, chromatin immunoprecipitation, and nucleosome position assays were performed in 5-aza treated cells. To evaluate antitumor activity in vivo, 5-aza was administered alone and in combination with temozolomide (TMZ) in a PDX glioma model harboring IDH1 R132H mutation. Results: 5-Aza treatment has been found to reduce cell growth and increase expression of glial fibrillary acid protein (GFAP). Chromatin immunoprecipitation and nucleosome position assay showed that the mechanism of increased GFAP expression induction is associated with histone modification and nucleosome repositioning of the GFAP promoter, respectively. In vivo, 5-aza treatment extended survival in IDH1 R132H mutant but not in an IDH1 wt glioma model. Additionally, 5-aza enhances the therapeutic effect of the DNA damaging agent TMZ in both subcutaneous and orthotopic PDX models of IDH1 R132H mutant glioma. Conclusion: 5-Aza provided a survival benefit as a single agent but worked best in combination with TMZ in 2 different IDH1 R132H mutant glioma models.